Na+ deposition in the fibrotic skin of systemic sclerosis patients detected by 23Na-magnetic resonance imaging - Kopp, Christoph; Beyer, Christian; Linz, Peter; Dahlmann, Anke; Hammon, Matthias; Jantsch, Jonathan; Neubert, Patrick; Rosenhauer, Daniela; Mueller, Dominik N.; Eckardt, Kai-Uwe; Schett, Georg; Luft, Friedrich C.; et al. (Rheumatology, 2017)
Skin fibrosis is the predominant feature of SSc and arises from excessive extracellular matrix deposition. Glycosaminoglycans are macromolecules of the extracellular matrix, which facilitate Na(+) accumulation in the skin. We used (23)Na-MRI to quantify Na(+) in skin. We hypothesized that skin Na(+) might accumulate in SSc and might be a biomarker for skin fibrosis.In this observational case-control study, skin Na(+) was determined by (23)Na-MRI using a Na(+) volume coil in 12 patients with diffuse cutaneous SSc and in 21 control subjects. We assessed skin fibrosis by the modified Rodnan skin score prior to (23)Na-MRI and on follow-up 12 months later.(23)Na-MRI demonstrated increased Na(+) in the fibrotic skin of SSc patients compared with skin from controls [mean (sd): 27.2 (5.6) vs 21.4 (5.3) mmol/l, P < 0.01]. Na(+) content was higher in fibrotic than in non-fibrotic SSc skin [26.2 (4.8) vs 19.2 (3.4) mmol/l, P < 0.01]. Furthermore, skin Na(+) amount was correlated with changes in follow-up modified Rodnan skin score (R(2) = 0.68).(23)Na-MRI detected increased Na(+) in the fibrotic SSc skin; high Na(+) content was associated with progressive skin disease. Our findings provide the first evidence that (23)Na-MRI might be a promising tool to assess skin Na(+) and thereby predict progression of skin fibrosis in SSc.
EVALuna:33997